Hollow fiber hemodialyzer with hydration layer and preparation method of hollow fiber hemodialyzer

CN119857189APending Publication Date: 2025-04-22成都欧赛医疗器械有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510141200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-22
Patent Text Reader

Abstract

The invention discloses a hollow fiber hemodialyzer with a hydration layer and a preparation method of the hollow fiber hemodialyzer. The hollow fiber hemodialyzer comprises the following raw materials in parts by weight: 10-35 parts of a polysulfone membrane material, 2-35 parts of a pore-forming agent, 25-80 parts of a solvent and 0-10 parts of a non-solvent. The inner diameter of the hollow fiber is 100-500 [mu] m, the wall thickness is 20-120 [mu] m, the membrane aperture is 0.5-10 nm, the pure water ultrafiltration rate is 50-2000 ml / m < 2 >. H.mmHg, and the maximum use transmembrane pressure is 700 mmHg. The hydrated layer is combined to the membrane surface and the membrane hole surface of the dialyzer, so that the affinity of the membrane surface and the membrane hole surface is improved, the biocompatibility of the dialyzer is improved, anaphylaxis in dialysis is reduced, the fluid design of dialyzer tows is optimized, dialysis is more sufficient, and the dialyzer quality is improved. And the probability of pore collapse and the risk of membrane rupture of tows are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical devices, and in particular to a hollow fiber hemodialyzer with a hydration layer and a preparation method thereof. Background Art

[0002] When chronic kidney disease (CKD) progresses to the end-stage renal disease (ESRD) stage, patients usually need to receive renal replacement therapy (such as peritoneal dialysis, hemodialysis or kidney transplantation). Given the global shortage of kidney sources, hemodialysis (HD) has become the main means of treating ESRD patients, and its importance in clinical treatment is self-evident. As the core component of this technology, the performance of the hollow fiber hemodialyzer directly affects the patient's treatment effect and quality of life. The hollow fiber hemodialyzer is mainly composed of semipermeable hollow fiber membranes, which use convection, diffusion and adsorption mechanisms to simulate the filtration function of human glomeruli to remove metabolic waste and excess water from the blood. However, the existing technology has shortcomings in many aspects:

[0003] First, the problem of the removal efficiency of medium and large molecular toxins. The current hollow fiber hemodialyzer still has room for improvement in the removal efficiency of medium and large molecular toxins, and some patients show insufficient dialysis. This problem may be related to the elution of hydrophilic additives (such as polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), etc.) during storage and use of the dialysis membrane material. During storage or use, the elution of additives such as porogen PVP may cause pore collapse in the dialysis membrane, thereby affecting the removal performance of medium and large molecular toxins; it may also cause the affinity of the dialysis membrane surface to decrease, making the dialysis membrane surface more likely to bind to proteins in the blood, causing platelet adhesion and activation, protein deterioration, etc., forming a protein layer on the membrane surface, thereby affecting the removal ability of medium and large molecular toxins and removing excess water in the human body. Specifically, the dialysis membrane mainly relies on asymmetric structure and membrane pores to remove solutes, so the size and distribution of the membrane pore size determine the solute transmission rate and selectivity during dialysis. Therefore, when a protein layer is formed on the surface of the hollow fiber membrane and the pore surface, the pore size and pore size distribution of the dialysis membrane will change, thereby affecting the removal efficiency of medium and large molecular toxins.

[0004] Secondly, there is the issue of biocompatibility. The fundamental problem of poor biocompatibility is that when the hollow fiber membrane material comes into contact with blood, a series of adverse reactions will be triggered after protein adhesion due to its surface affinity or other reasons, such as complement activation, oxidative stress, platelet aggregation and activation, coagulation mechanism activation, inflammation and other reactions. Although the biocompatibility of commercial hemodialysis membrane materials has been significantly improved through certain modification methods, patients still experience allergies, oxidative stress, inflammation and other reactions during use. This may be related to the modification technology of the membrane material and the physical and chemical properties of the inner surface of the membrane. Therefore, appropriately increasing the affinity of the inner surface of the hollow fiber membrane and reducing adverse reactions are the key to improving biocompatibility.

[0005] Third, the quality and life of the dialyzer. Most of the common hollow fiber hemodialyzer products on the market are dry dialyzers, but such products occasionally break the membrane during use, which greatly reduces the patient's treatment effect and quality of life, and increases the risk of infection for patients. The most likely reasons for this are: 1. When the dry membrane dialyzer product is drying, some of the filaments may be blown off or stretched, and there is usually no way to detect whether the product is broken after drying; 2. During the dialysis process, due to the weak affinity of the membrane surface, proteins and other macromolecules are easily deposited on the membrane surface, which may cause the mechanical stress of the dialysis membrane to decrease. Therefore, effectively avoiding the reduction of mechanical strength and protein adsorption of hollow fiber membranes is the key to improving patient treatment effects and reducing unnecessary risks.

[0006] Finally, there is the problem of structural design. The complexity of the dialyzer's internal structure will cause uneven blood flow during dialysis, thus affecting the dialysis effect. The flow channel design, filament filling rate and filament state inside the dialyzer will affect the blood flow dynamics. Uneven flow may cause the dialyzer's dialysis efficiency to decrease, resulting in insufficient dialysis. Therefore, optimizing the design of the dialyzer's internal structure to achieve uniform blood flow is an important way to improve the dialysis effect. Summary of the invention

[0007] The purpose of the present invention is to provide a hollow fiber hemodialyzer with a hydration layer and a preparation method thereof, so as to solve the problems existing in the prior art in terms of macromolecular toxin removal efficiency, biocompatibility, quality, service life and structure of hollow fiber hemodialyzers.

[0008] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a hollow fiber hemodialyzer with a hydration layer, comprising the following raw materials in parts by weight: 10 to 35 parts of polysulfone membrane material, 2 to 35 parts of pore former, 25 to 80 parts of solvent, and 0 to 10 parts of non-solvent.

[0009] Furthermore, the polysulfone membrane material includes: bisphenol A polysulfone, polyethersulfone, polyarylsulfone, hydroxy polyethersulfone, and sulfonated polyethersulfone.

[0010] Furthermore, the pore-forming agent is any one or any combination of polyvinyl pyrrolidone, diethylene glycol, polyvinyl alcohol, polyethylene glycol, sodium alginate, polyacrylamide, polypropylene alcohol, and N-(2-hydroxypropyl)methylpropylamide.

[0011] Furthermore, the molecular weight of the polyvinyl pyrrolidone is 10,000-400,000, and the molecular weight of the diethylene glycol is 1,000-20,000.

[0012] Furthermore, the solvent is any one or any combination of dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

[0013] Furthermore, the non-solvent is any one or any combination of purified water, methanol, propylene glycol, glycerol, n-butanol, and diethylene glycol.

[0014] The present invention also provides a method for preparing a hollow fiber hemodialyzer having a hydration layer, comprising the following steps: S1. Preparation of spinning solution 10-35 parts of polysulfone membrane material, 2-35 parts of pore-forming agent, 25-80 parts of solvent and 0-10 parts of non-solvent are heated and stirred to obtain a polymer solution, and the polymer solution is filtered, degassed and aged to obtain a spinning solution; S2, dry-wet spinning The spinning solution and the core solution are extruded through the outer annular slit and the inner hole of two concentric hollow fiber spinning nozzles, respectively, to form a hollow fiber membrane with a five-layer structure, namely, the outer surface cortex, the outer support layer, the separation layer, the inner support layer, and the inner surface cortex. There are curved, staggered and interlinked channels between the layers, and the inner surface cortex is the main area for screening materials. It is successively passed through an air bath and a coagulation bath to undergo phase transformation and solidification to form a membrane, and then stretched and wound in a plasticizing bath, with a winding speed of 5-60 m / min. S3. Fiber post-processing The wound hollow fiber membrane in S2 is treated in water at a temperature of 25-70°C for 6-24 hours, during which the water needs to be changed continuously, and the residual solvent and pore-forming agent are removed, and then dried in hot air at a temperature of 40-80°C for 10-1200 min; S4. Hydration layer treatment After the hollow fiber hemodialyzer has been treated with membrane rupture detection, rinse it with 40-100 ℃ sterile water for 5-20 minutes to fully moisten the hollow fiber membrane. Then, inject sterile water into the dialyzer shell and hollow fiber bundles to make the inner and outer surfaces of the hollow fiber membrane, as well as the inner and outer support layers and separation layers, full of water. Part of the water will form bound water to form a hydration layer on the membrane surface.

[0015] Furthermore, the heating and stirring conditions in S1 are stirring and dissolving at a temperature of 40-95° C. for 4-48 hours.

[0016] Furthermore, the specific conditions for extruding the hollow fiber membrane in S2 are as follows: the temperatures of the spinneret and the spinning solution are maintained at 40~80°C and 40~60°C respectively, the air humidity is maintained at 20~80%, the spinning solution pressure is 0.1~0.3 MPa, the spinning speed is 2~10 ml / min, and the core liquid flow rate is 10~50 ml / min; the core liquid contains 20~90 parts by weight of solvent and 10~80 parts by weight of pure water, the coagulation bath is purified water, and the coagulation bath temperature is 20~60°C.

[0017] Furthermore, the presence of the hydration layer can effectively prevent the adsorption of proteins and blood cells in the blood on the surface of the hollow fibers, thereby reducing oxidative stress, allergies, inflammation, coagulation and other phenomena during the dialysis process.

[0018] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects: The present invention provides a hollow fiber hemodialyzer with a hydration layer for the treatment of acute and chronic kidney disease, wherein the inner diameter of the hollow fiber is 100-500 μm, the wall thickness is 20-120 μm, the membrane pore size is 0.5-10 nm, and the pure water ultrafiltration rate is 50-2000 ml / m 2 .h.mmHg, the maximum transmembrane pressure is 700 mmHg. Due to the presence of the hydration layer on the membrane surface and the membrane pore surface, the surface affinity of the hollow fiber membrane of the dialyzer is increased, which makes the dialyzer have good biocompatibility and can effectively improve the adsorption and deformation of plasma proteins during dialysis, thereby effectively inhibiting platelet aggregation and activation, complement activation, oxidative stress, reducing hemolysis rate, and improving patients' allergic symptoms such as itching during the dialysis process or after the end of treatment. By introducing the hydration layer, from the structure of the dialyzer, the membrane pore size and membrane pore distribution of the dialyzer are relatively stable, the flow channel design inside the dialyzer is optimized, and the flow is uniform, so that the dialysis efficiency is improved. In terms of product quality and service life, during the product preparation process, the dialyzer drying process is eliminated, and the probability of filament bundle membrane rupture is reduced. The presence of the hydration layer supports the membrane pore structure in the filament bundle, and it is not easy to cause pore collapse and other behaviors, which improves the mechanical strength of the filament bundle and reduces the risk of product membrane rupture. Specifically:

[0019] The hollow fiber hemodialyzer with a hydration layer provided by the present invention improves the affinity of the membrane surface and the membrane pore surface by combining the hydration layer to the dialyzer membrane surface and the membrane pore surface, improves the biocompatibility of the dialyzer, reduces the allergic reaction during dialysis, optimizes the fluid design of the dialyzer filament bundle, makes the dialysis more sufficient, reduces the probability of pore collapse and the risk of filament bundle rupture, thereby achieving the purpose of improving the treatment effect and survival time of patients in an economical and convenient way. DETAILED DESCRIPTION

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0025] Example 1 Add 23 parts of hydroxy polyether sulfone, 5 parts of polyacrylamide, 68 parts of N, N'-dimethylformamide and 4 parts of methanol into a container equipped with a stirrer, a thermometer and a pressure gauge, and stir and dissolve them at 70-90℃ for 18 hours to fully mix the spinning solution. The mixed spinning solution must be filtered first, and then placed at 50-70℃ and -0.06--0.1Mpa for degassing for 8-16 hours before spinning.

[0026] The spinning solution and the core liquid are extruded through the outer annular seam and inner hole of two concentric hollow fiber spinning nozzles, respectively. The spinneret and the spinning solution temperature are maintained at 55°C and 50°C, respectively, the air humidity is maintained at 70-80%, the spinning solution pressure is 0.2MPa, the spinning speed is 3.5ml / min, and the core liquid flow rate is 25ml / min. After passing through an air bath with a height of 32cm, the nascent fiber enters a coagulation bath with a temperature of 25-50°C for phase inversion solidification to form a film, and then is stretched and wound in a plasticizing bath, with a winding speed of 17m / min. The core liquid contains 40 parts by weight of N, N'-dimethylformamide and 60 parts by weight of purified water, and the coagulation bath is pure water. The spun hollow fiber bundle is soaked in water at a temperature of 45-50°C for 6 hours to remove residual solvents and pore-forming agents.

[0027] The soaked filament bundles were dried in dry hot air at 40-50°C for 120 minutes and assembled into dialyzer products through the back end. After the membrane rupture test, the products were rinsed with 80°C sterile water for 10 minutes, and then the sterile water was injected into the hollow fiber membrane and the product shell. After radiation sterilization, a hollow fiber hemodialyzer with a hydration layer was obtained. The fiber inner diameter was 230μm, the pore size was 8.2nm, the pure water ultrafiltration rate was 520ml / m²·h·mmHg, the β2 microglobulin clearance rate was 80ml / min, the hemolysis rate was 2.1%, and the static protein adsorption content was 31.62μg / cm².

[0028] Example 2 Add 25 parts of polyethersulfone, 5 parts of polyvinylpyrrolidone, 67 parts of N,N'-dimethylformamide and 3 parts of glycerol into a container equipped with a stirrer, a thermometer and a pressure gauge, and stir and dissolve them at 70-90℃ for 16 hours to fully mix the spinning solution. The mixed spinning solution must be filtered first, and then placed at 50-70℃ and -0.06--0.1Mpa for degassing for 8-16 hours before spinning.

[0029] The spinning solution and the core liquid are extruded through the outer annular seam and inner hole of two concentric hollow fiber spinning nozzles, respectively. The spinneret and the spinning solution temperature are maintained at 55°C and 50°C, respectively. The air humidity is maintained at 70-80%, the spinning solution pressure is 0.22MPa, the spinning speed is 3.8ml / min, and the core liquid flow rate is 28ml / min. After passing through an air bath with a height of 25cm, the nascent fiber enters a coagulation bath with a temperature of 25-50°C for phase inversion solidification to form a film, and then is stretched and wound in a plasticizing bath at a winding speed of 21m / min. The core liquid contains 45 parts by weight of N, N'-dimethylformamide and 55 parts by weight of purified water, and the coagulation bath is pure water. The spun hollow fiber bundle is soaked in water at a temperature of 45-50°C for 6 hours to remove residual solvents and pore-forming agents.

[0030] The soaked filament bundles were dried in dry hot air at 40-50°C for 150 minutes, assembled into dialyzer products through the back end, and the products that passed the membrane rupture test were rinsed with 70°C sterile water for 8 minutes. The sterile water was then injected into the hollow fiber membrane and the product shell. After radiation sterilization, a hollow fiber hemodialyzer with a hydration layer was obtained. The fiber inner diameter was 250μm, the pore size was 6.7nm, the pure water ultrafiltration rate was 440ml / m²·h·mmHg, the β2 microglobulin clearance rate was 72ml / min, the hemolysis rate was 2.6%, and the static protein adsorption content was 42.37μg / cm².

[0031] Example 3 Add 22 parts of sulfonated polyethersulfone, 6 parts of sodium alginate, 69 parts of N-methylpyrrolidone, and 3 parts of propylene glycol into a container with a stirrer, a thermometer, and a pressure gauge, and stir and dissolve at 70~90℃ for 18 hours to fully stir the spinning solution. The stirred spinning solution must be filtered first, and then left to stand and degas for 8~16 hours at 50~70℃ and -0.06~-0.1Mpa before spinning. The spinning solution and the core solution are extruded through the outer annular seam and inner hole of two concentric hollow fiber spinning nozzles, respectively. The spinneret and spinning solution temperatures are maintained at 55℃ and 50℃, respectively, the air humidity is maintained at 70~80%, the spinning solution pressure is 0.2MPa, the spinning speed is 4.5ml / min, and the core solution flow rate is 30ml / min. After passing through an air bath with a height of 35 cm, the nascent fiber enters a coagulation bath with a temperature of 25-50° C. to undergo phase inversion solidification into a film, and then is drawn and wound in a plasticizing bath at a winding speed of 20 m / min. The core liquid comprises 55 parts by weight of N, N'-dimethylformamide and 45 parts by weight of purified water, and the coagulation bath is pure water. The spun hollow fiber bundle is soaked in water at a temperature of 45-50° C. for 6 hours to remove residual solvent and pore-forming agent. The soaked filament bundles were dried in dry hot air at 40-50°C for 100 minutes and assembled into dialyzer products through the back end. After the membrane rupture test, the products were rinsed with 90°C sterile water for 12 minutes, and then the sterile water was injected into the hollow fiber membrane and the product shell. After radiation sterilization, a hollow fiber hemodialyzer with a hydration layer was obtained. The fiber inner diameter was 210μm, the pore size was 7.7nm, the pure water ultrafiltration rate was 660ml / m²·h·mmHg, the β2 microglobulin clearance rate was 82ml / min, the hemolysis rate was 1.9%, and the static protein adsorption content was 26.68μg / cm².

[0032] Example 4 The difference from Example 1 is: 10 parts of hydroxy polyether sulfone, 2 parts of polyacrylamide, 25 parts of N,N'-dimethylformamide, 4 parts of methanol; The rest of the process was carried out according to Example 1.

[0033] Example 5 The difference from Example 1 is: 23 parts of hydroxy polyether sulfone, 5 parts of polyacrylamide, 68 parts of N,N'-dimethylformamide; The rest of the process was carried out according to Example 1.

[0034] Example 6 The difference from Example 1 is: 35 parts of hydroxy polyether sulfone, 35 parts of polyacrylamide, 80 parts of N,N'-dimethylformamide, 10 parts of methanol; The rest of the process was carried out according to Example 1.

[0035] Example 7 The difference from Example 1 is: 35 parts of hydroxy polyether sulfone, Any one or any combination of polyvinyl pyrrolidone, diethylene glycol, polyvinyl alcohol, polyethylene glycol, sodium alginate, polyacrylamide, polyacryl alcohol, N-(2-hydroxypropyl)methylpropylamide, 35 parts 80 parts of any one or any combination of dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide, 10 parts of any one or any combination of purified water, methanol, propylene glycol, glycerol, n-butanol, and diethylene glycol; The rest of the process was carried out according to Example 1.

[0036] Comparative Example 1 Add 22 parts of polyethersulfone, 6 parts of polyvinylpyrrolidone, and 72 parts of N,N'-dimethylformamide into a container with a stirrer, a thermometer, and a pressure gauge, and stir and dissolve at 70~90℃ for 18 hours to fully stir the spinning solution. The stirred spinning solution must be filtered first, and then left to stand and degas for 8~16 hours at 50~70℃ and -0.06~-0.1Mpa before spinning. The spinning solution and the core solution are extruded through the outer annular seam and inner hole of two concentric hollow fiber spinning nozzles, respectively. The spinneret and spinning solution temperatures are maintained at 55℃ and 50℃, respectively, the air humidity is maintained at 70~80%, the spinning solution pressure is 0.2MPa, the spinning speed is 4.0ml / min, and the core solution flow rate is 25ml / min. After passing through an air bath with a height of 33 cm, the nascent fiber enters a coagulation bath with a temperature of 25-50°C to undergo phase inversion and solidification into a film, and then is stretched and wound in a plasticizing bath, with a winding speed of 25 m / min. The core liquid contains 50 parts by weight of N, N'-dimethylformamide and 50 parts by weight of purified water, and the coagulation bath is pure water. The spun hollow fiber bundle is soaked in water at a temperature of 45-50°C for 6 hours to remove residual solvent and pore-forming agent. The fiber inner diameter is 196μm, the pore size is 4.6nm, the pure water ultrafiltration rate is 380ml / m²·h·mmHg, the β2 microglobulin clearance rate is 61ml / min, the hemolysis rate is 4.2%, and the static protein adsorption content is 137.24μg / cm².

[0037] The products of Examples 1-3 and Comparative Example 1 were tested for solute removal rate, and the results are shown in Table 1: Table 1 Example 1 Example 2 Example 3 Comparative Example 1 Urea clearance rate (ml / min) 196 192 198 182 Creatinine clearance (ml / min) 192 190 194 176 Phosphate clearance (ml / min) 188 183 191 178 <![CDATA[Vitamin B 12 Clearance rate (ml / min)]]> 156 152 158 134 <![CDATA[β2 - microglobulin clearance rate (ml / min)]]> 80 72 82 61 As can be seen from Table 1, the hollow fiber hemodialyzer with a hydration layer has a more complete solute removal due to the optimization of its fluid channel.

[0038] The products of Examples 1-3 and Comparative Example 1 were subjected to other performance tests, and the results are shown in Table 2: Table 2 performance Example 1 Example 2 Example 3 Comparative Example 1 Pure water contact angle 65.1° 70.6° 62.4° 78.2° Static adsorption capacity of bovine serum albumin 31.62 μg / cm² 42.37 μg / cm² 26.68 μg / cm² 137.24 μg / cm² As can be seen from Table 2, the hollow fiber hemodialyzer with a hydration layer has a layer of bound water on the membrane surface and the membrane pore surface, and the surface affinity is strong, which reduces the water contact angle and protein adsorption, improves the hydrophilicity of the membrane surface and the membrane pore surface, and enhances its anti-protein adsorption ability, which can effectively reduce the patient's itching and other allergic symptoms during dialysis treatment.

[0039] The products of Examples 4-7 were tested for solute removal rate, and the results are shown in Table 3: Table 3 Example 4 Example 5 Example 6 Example 7 Urea clearance rate (ml / min) 197 193 196 194 Creatinine clearance (ml / min) 194 192 195 193 Phosphate clearance (ml / min) 187 184 190 188 <![CDATA[Vitamin B 12 Clearance rate (ml / min)]]> 156 153 159 158 <![CDATA[β2-microglobulin clearance rate (ml / min)]]> 82 74 83 85 It can be seen from Table 3 that the test results of other embodiments of the present invention show more complete solute removal.

[0040] Finally, it should be noted that: The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hollow fiber hemodialyzer having a hydration layer, characterized in that: The invention comprises the following raw materials in parts by weight: 10 to 35 parts of polysulfone membrane material, 2 to 35 parts of pore-forming agent, 25 to 80 parts of solvent and 0 to 10 parts of non-solvent.

2. The hollow fiber hemodialyzer with a hydration layer according to claim 1, characterized in that: The polysulfone membrane materials include: bisphenol A polysulfone, polyethersulfone, polyarylsulfone, hydroxy polyethersulfone, and sulfonated polyethersulfone.

3. The hollow fiber hemodialyzer with a hydration layer according to claim 1, characterized in that: The pore-forming agent is any one or any combination of polyvinyl pyrrolidone, diethylene glycol, polyvinyl alcohol, polyethylene glycol, sodium alginate, polyacrylamide, polyacryl alcohol, and N-(2-hydroxypropyl)methylpropylamide.

4. The hollow fiber hemodialyzer with a hydration layer according to claim 3, characterized in that: The molecular weight of the polyvinyl pyrrolidone is 10,000-400,000, and the molecular weight of the diethylene glycol is 1,000-20,000.

5. The hollow fiber hemodialyzer with a hydration layer according to claim 1, characterized in that: The solvent is any one or any combination of dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide.

6. The hollow fiber hemodialyzer with a hydration layer according to claim 1, characterized in that: The non-solvent is any one or any combination of purified water, methanol, propylene glycol, glycerol, n-butanol, and diethylene glycol.

7. The method for preparing a hollow fiber hemodialyzer having a hydration layer according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparation of spinning solution 10-35 parts of polysulfone membrane material, 2-35 parts of pore-forming agent, 25-80 parts of solvent and 0-10 parts of non-solvent are heated and stirred to obtain a polymer solution, and the polymer solution is filtered, degassed and aged to obtain a spinning solution; S2, dry-wet spinning The spinning solution and the core solution are extruded through the outer annular slit and the inner hole of two concentric hollow fiber spinning nozzles to form a hollow fiber membrane with a five-layer structure, which is then phase-converted and solidified in an air bath and a coagulation bath, and then stretched and wound in a plasticizing bath at a winding speed of 5-60 m / min. S3. Fiber post-processing The hollow fiber membrane wound up in S2 is dried in hot air at a temperature of 40-80° C. for 10-1200 min after removing the residual solvent and pore-forming agent with water; S4. Hydration layer treatment After the hollow fiber hemodialyzer has been treated with membrane rupture detection, it is rinsed with 40-100 ℃ sterile water for 5-20 minutes to fully moisten the hollow fiber membrane. Then, sterile water is injected into the dialyzer shell and the hollow fiber bundle to allow the inner and outer surfaces of the hollow fiber membrane, as well as the inner and outer support layers and separation layers to be filled with water. Part of the water will form bound water to form a hydration layer on the membrane surface.

8. The method for preparing a hollow fiber hemodialyzer having a hydration layer according to claim 7, characterized in that: The heating and stirring conditions in S1 are as follows: the temperature is 40-95° C. and the stirring and dissolving is performed for 4-48 hours.

9. The method for preparing a hollow fiber hemodialyzer having a hydration layer according to claim 7, characterized in that: The specific conditions for extruding the hollow fiber membrane in S2 are as follows: the temperatures of the spinneret and the spinning solution are maintained at 40~80°C and 40~60°C respectively, the air humidity is maintained at 20~80%, the spinning solution pressure is 0.1~0.3 MPa, the spinning speed is 2~10 ml / min, and the core liquid flow rate is 10~50 ml / min; the core liquid contains 20~90 parts by weight of solvent and 10~80 parts by weight of pure water, the coagulation bath is purified water, and the coagulation bath temperature is 20~60°C.

10. The method for preparing a hollow fiber hemodialyzer having a hydration layer according to claim 7, characterized in that: The step of removing the residual solvent and pore-forming agent in S3 is specifically to treat the mixture in water at a temperature of 25 to 70° C. for 6 to 24 hours, during which the water needs to be changed continuously.